The Effect of Inquiry Learning Model of Student’s Learning Outcomes in Science Materials about Style at Grade IV SDN Mentaos Gudo Jombang - Ines Stesia Ramadani; Desty Rochmania (Prodi PGSD Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2022)
Education is the most important factor in determining one’s future. As well as helping students think critically, one of the factors causing low learning outcomes is an inappropriate learning process. Thematic learning on science material about style is carried out by educators in class IV SDN Mentaos by using lectures, discussion, practice questions that tend to be teacher center, causing students to feel bored, bored and even tend to dislike the material being taught and students become not enthusiastic in learning. This can be done by giving students the opportunity to think critically by using the inquiry learning model, because with this inquiry model students will be directly involved in critical thinking, asking questions, and conducting experiments, so that students’ knowledge of the subject matter is also stonger and meaningful. This study aims to determine the effect of the inquiry learning model on student learning outcomes in science subjects about the style of class IV SD. This research is a quantitative research with the type of research Pre-Experimental Design with a research design of One Group Pre Test Post Test Design. The population of this study is the entire class IV totaling 25 students consisting of 13 boys and 12 girls. The data analysis in this study used normality test analysis, and t-test with the help of SPSS (Statistical Package for Social Science) software. The results of this study indicate that there is an effect of learning science material on the style of fourth grade studets at SDN Mentaos Gudo Jombang with a significant level of 0.000. The significant value shows 0.000 < 0.05. So Ho is rejected and H1 is accepted. Which means, in this study the variable using the inquiry learning model has an effect on student learning outcomes. Keywords: effect, inquiry learning model, learning outcomes.